2020
DOI: 10.3390/agronomy10010104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biochar Application in a Sorghum Crop under Greenhouse Conditions: Growth Parameters and Physicochemical Fertility

Abstract: Application of biochar from vine shoots (Vitis vinifera L.) as an organic amendment in the soil is an alternative agricultural management of interest. The behavior of this type of amendment in the soil requires more information to adjust the pyrolysis conditions in order to obtain a high-quality biochar. The aim of this work is determining the influence of the application of this type of biochar on the soil-plant system. For this purpose, an agronomic test was performed in greenhouse pots. A randomized tri-fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 57 publications
3
27
0
Order By: Relevance
“…However, depending on the experimental conditions and especially on soil-nutrient availability, decreases in AMF root colonization have also been reported [ 18 , 21 ]. In this particular experiment, it was confirmed that biochar had a positive effect on AMF development in the sandy-loam texture (S1); nevertheless, the higher activity of mycorrhized roots or number of AMF spores did not result in any marked increase in the biological crop yield, as reported in a previous publication [ 30 ]. The obtained results in B600 treatment at high doses in the clay-loam substrate, as mentioned above, showed the minimum value of root colonization and the maximum value for the number of AMF spores, which leads to the conclusion that the sporulation strategy by the mycorrhiza prevailed in this treatment over root colonization.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…However, depending on the experimental conditions and especially on soil-nutrient availability, decreases in AMF root colonization have also been reported [ 18 , 21 ]. In this particular experiment, it was confirmed that biochar had a positive effect on AMF development in the sandy-loam texture (S1); nevertheless, the higher activity of mycorrhized roots or number of AMF spores did not result in any marked increase in the biological crop yield, as reported in a previous publication [ 30 ]. The obtained results in B600 treatment at high doses in the clay-loam substrate, as mentioned above, showed the minimum value of root colonization and the maximum value for the number of AMF spores, which leads to the conclusion that the sporulation strategy by the mycorrhiza prevailed in this treatment over root colonization.…”
Section: Discussionsupporting
confidence: 87%
“…For the specific results of our experiment, no differences in P content were found on substrates or plant tissue [ 30 ]; however, a positive correlation between AMF activity and Pseudomonas abundance was confirmed for the sandy-loam substrate (see Table S4 ).…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations